Additional records of the plant bug genus Hallodapus Fieber from Thailand, with proposal of a new synonymy (Hemiptera: Heteroptera: Miridae: Phylinae) - Yasunaga, Tomohide; Yamada, Kazutaka; Artchawakom, Taksin (Zootaxa, 2013)
Although species of the genus Hallodapus Fieber from Thailand were documented in our recent paper (Yasunaga et al., 2013), subsequent sorting of specimens and fieldworks have provided two additional species. These are unequivocally identical to Hallodapus centrimaculatus (Poppius) and H. fasciatus (Poppius), which have not been recorded from Thailand. Further, H. fenestratus Linnavuori, originally described from Japan, is found to be conspecific with H. centrimaculatus during the confirmation of the accurate identities of the Thai specimens.